Maternal Health Transformation: Harnessing IoMT for Advanced Risk Assessment and Monitoring - Panchal, Dipali; Vaghela, Krunal (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This research introduces a groundbreaking approach to enhance maternal health in remote developing regions through IoT-enabled wearable sensing technology. Despite persistent challenges in reducing maternal and fetal mortality rates, the integration of intelligent machine learning algorithms into healthcare systems presents significant promise. The proposed system not only monitors maternal well-being but also delivers real-time health updates to both mothers and their families. Emphasizing the critical aspect of accuracy in technological solutions, particularly in remote developing regions, this research highlights the potential transformative impact of IoT-driven wearables on maternal and infant healthcare. The study aims to contribute valuable insights to the ongoing global efforts focused on reducing maternal and fetal mortality rates through innovative and effective technological interventions.